Representasi Eksistensi Perempuan dalam Novel Terusir Karya Hamka (Kajian Sastra Feminis) - Syifa Fadiyah; Nawawi Nawawi (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2023)
This study aims to describe the forms of women's existence representation in the novel "Terusir" by Hamka. The research data was collected using a qualitative descriptive method with a literary feminism approach. Data collection techniques included library research, reading, and note-taking. The data analysis employed a descriptive approach, involving data classification, data reduction, data presentation, and drawing conclusions. The findings of this study reveal the forms of women's existence representation in three aspects. Firstly, the character of Mariah depicts various characteristics of women, such as honesty, independence, perseverance, patience, weakness, bravery, fear, goodness, and submission. Secondly, women's existence is manifested as a strategy of resistance, including their ability to work, become intellectuals, bring about social transformations, and reject gender discrimination. Thirdly, Mariah experiences gender injustices, such as marginalization, subordination, stereotypes, violence, and work burden.